Developing Formative Assessment AKM-Based for Recount Text in Reading Skill for Grade X SMA Negeri 1 Pangkalan Susu North Sumatera - Agustina Syafriani; Rahmad Husein; Lidwina Sri Ardiasih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to 1) explain how the AKM-based recount text formative assessment in class X students' reading skills is developed, 2) describe the validity of AKM-based recount text formative assessment on class X students' reading skills, 3) describe the effectiveness of AKM-based recount text formative assessment in reading skills of class X students. This study uses the Research and Development (R&D) model, consisting of three main stages, namely: preliminary study, development and design of the assessment, validation of the assessment sheet. The results of the study describe the process of developing formative assessment through the stages of literature review, needs analysis, drafting, design, testing, revision, and expert validation. The validation process was carried out on question validation and expert validation, the results of the validation of the questions showed a valid, reliable formative assessment, the level of difficulty was in the "Medium" criteria and the differentiating power was in the "Good" criteria. The product validity results were declared according to the content expert validator with an average score of 96.74 on the "Very Good" criterion, the format expert validator with an average score of 92.42 on the "Very Good" criterion, and the linguist validator with an average score average 82.81 on the "Good" criteria. The overall average of the validation aspect is 90.66 in the "Very Good" criterion. The effectiveness of the process is based on student learning outcomes in the 2 trials with an average score of 59.17 and 58.00 respectively which is below the KKM = 70. This means that the formative assessment product does not meet the criteria of effectiveness based on cognitive processes, based on teacher feedback and students on formative assessment sheets the average results of teacher and student feedback were 82.50 and 85.92 respectively in the "Good" criterion so that formative assessment products met the effective criteria.